2020
DOI: 10.1182/blood-2020-137630
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose-Escalation Trial of CD19/CD20 Bispecific Chimeric Antigen Receptor (CAR) T-Cells for the Treatment of Relapsed or Refractory B-Cell Lymphomas and Chronic Lymphocytic Leukemia

Abstract: Background: Single-input anti-CD19 CAR T-cells have demonstrated clinical efficacy for relapsed or refractory (R/R) non-Hodgkin B-cell lymphoma (NHL) and chronic lymphocytic leukemia (CLL). Despite excellent response rates, over 50% of CD19 CAR T-cell recipients relapse. Preclinical data show engineering of bispecific anti-CD19/CD20 CAR T-cells via lentiviral transduction effectively targets tumor cells and overcomes antigen escape (Zah E et al., Cancer Immunol Res, 2016). Based on these promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Studies have shown that the composition of T cell subsets and their metabolic adaptability are closely related to their antitumor activity. CD19 CAR-T cells that were manufactured from purified CD4+ or CD8+ Tcm or Tn have been shown to have enhanced metabolic adaptability and long-term anti-tumor response [ 18 , 19 ]. CD19 CART derived from TSCM showed good long-term response as compared to CD19 CART standardly manufactured, however it is unclear whether just having more Tscm or the decreased glycolysis of the Tscm drives the long-term response [ 20 ].…”
Section: T Cell Metabolic Reprogrammingmentioning
confidence: 99%
“…Studies have shown that the composition of T cell subsets and their metabolic adaptability are closely related to their antitumor activity. CD19 CAR-T cells that were manufactured from purified CD4+ or CD8+ Tcm or Tn have been shown to have enhanced metabolic adaptability and long-term anti-tumor response [ 18 , 19 ]. CD19 CART derived from TSCM showed good long-term response as compared to CD19 CART standardly manufactured, however it is unclear whether just having more Tscm or the decreased glycolysis of the Tscm drives the long-term response [ 20 ].…”
Section: T Cell Metabolic Reprogrammingmentioning
confidence: 99%
“…Our group recently reported promising early outcomes in a phase 1 dose-escalation study evaluating a novel bi-specific CAR-T construct targeting CD19 and CD20 in 3 heavily pre-treated patients with R/R B-cell NHL. No dose-limiting toxicities occurred and 2 patients remained in ongoing CR at 6-month data cut-off (NCT04007029) (25). Wei et al reported on a novel CAR-T construct targeting CD19 and CD22 in 12 R/R DHL patients and reported a median OS and PFS that were both NR (median follow-up, 12.1 months) (26).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to FDA approval of CD19-directed chimeric antigen T-cell receptor (CAR-T) therapies, patients with chemo-refractory disease or those relapsing after high-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (ASCT) had limited therapeutic options and poor outcomes. The SCHOLAR-1 study, published prior to the implementation of CAR-T therapy, showed that patients with refractory BCL to first-or second-line chemotherapy, or relapsing less than 12 months after ASCT had dismal outcomes, including an overall response rate (ORR) of 26% (95% CI [21][22][23][24][25][26][27][28][29][30][31] to subsequent standard therapy and a median overall survival (OS) of 6.3 months (95% CI 5.9-7.0) (2). Chemoresistance is more pronounced in DHL/THL with inferior complete response (CR) rates (3) and post-ASCT outcomes (4) compared to their non-DHL/THL counterparts.…”
Section: Introductionmentioning
confidence: 99%